A Clinical Decision-Making Framework for the Use of Video Gaming as a Therapeutic Modality - Espy, Debbie; Reinthal, Ann; Dal Bello-Haas, Vanina (Frontiers in Neurology, 2021)
Virtual reality and video gaming offer modulation of more exercise and motor learning parameters simultaneously than other modalities; however, there is a demonstrated need for resources to facilitate their effective use clinically. This article presents a conceptual framework to guide clinical decision-making for the selection, adaptation, modulation and progression of virtual reality or gaming when used as a therapeutic exercise modality, as well as two cases as exemplars. This framework was developed by adapting the steps of theory derivation, whereby concepts and parent theories are brought together to describe a new structure or phenomenon of interest. Specifically, motor learning theory, integrated motor control theory, Gentile’s Taxonomy of Tasks, and therapeutic exercise principles were integrated to develop this framework. It incorporates person (body segment), environmental, and task demands; each demand is comprised of realm, category, choice and continuum parameters as motor training considerations and alternatives for decision-making. This framework: 1) provides structure to guide clinical decisions for effective and safe use of virtual reality or gaming to meet therapeutic goals and requirements, 2) is a concise and organized method to identify, document, and track the therapeutic components of protocols and client progression over time; 3) can facilitate documentation for reimbursement and communication among clinicians; and, 4) informs research questions and methods, and 5) structures student learning.